Authenticity, Credibility, and Cultural Context: An Integrated Model of Influencer Marketing in Collectivistic Societies - Fadli; Nasution, Muhammad Dharma Tuah Putra; Qamariah, Inneke; Zulkarnain, Siti Hafsah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Influencer marketing thrives in Indonesia’s collectivistic culture, where community trust shapes consumer behavior. This study aims to test the Cultural Contingency Theory of Digital Influence, examining how authenticity influences credibility and digital engagement among influencers on Instagram and TikTok. A mixed-methods approach was employed, analyzing data from 152 influencers over eight weeks. The study utilized a natural language processing model tailored for the Indonesian language to assess authenticity, alongside validated scales for credibility, engagement, and consumer skepticism, followed by structural equation modeling for hypothesis testing. Findings reveal that authenticity strongly enhances credibility, which in turn drives digital engagement through likes, comments, and shares. Nano influencers excel in building credibility through authentic, community-driven content reflecting values like mutual cooperation (gotong royong), while micro influencers boost engagement with broader reach. Consumer skepticism weakens the authenticity–credibility link, particularly when content lacks cultural resonance, such as moral character. Engagement is higher in Java than Sumatra, with TikTok favoring raw authenticity and Instagram emphasizing curated aesthetics. This study validates a culturally contingent model, offering insights for tailored marketing strategies, although it is limited by its focus on the standard Indonesian language and short study duration.